A Short Form of the Lichtenberg Financial Decision Rating Scale. Issue 3 (3rd May 2020) - Lichtenberg, Peter A.; Gross, Evan; Campbell, Rebecca
ABSTRACT: Objectives : This article examines the convergent validity and clinical utility of the 34-item short form of the Lichtenberg Financial Decision Rating Scale (LFDRS-SF). A briefer scale can lead to enhanced and efficient use of a person-centered approach to the assessment of financial decision-making. Methods : Using data on 200 community-dwelling older adults from Lichtenberg and colleagues (2017a), convergent validity was examined with cognitive and financial management measures using a correlational and regression approach. Receiver operating curve analyses for predicting decision-making ability classification and suspected financial exploitation classification were used to evaluate clinical utility. Results : The LFDRS-SF total risk score was significantly correlated with both cognitive and financial management measures, and the regression analysis predicted 9% of the LFDRS-SF measure. These results demonstrate not only convergent validity, but also the conceptual and empirical uniqueness of financial decision-making. Conclusions : The LFDRS-SF is a valid tool to assess real-world financial decision-making abilities. Clinical Implications : The LFDRS-SF offers an efficient way to assess financial decision-making. Training on the tool and automatic scoring and recommendations for next steps can be found at https://olderadultnestegg.com